Pengembangan Produk Promosi Perpustakaan Berbasis Video Animasi 2D di Perpustakaan SMA Negeri 8 Malang - Septiani Rosyidah; Kusubakti Andajani; Moh. Safii (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Library plays a role as a learning resource center for school residents by providing library materials to support learning. However, the school library is underutilized properly as a learning support. The purpose of this research and development is to produce 2D animation video-based library promotion products that meet the aspects of feasibility, accuracy, and attractiveness. 2D animated video products are made with reading benefit materials and a 15-minute reading program in schools. This study used a research and development model for R&D Borg and Gall. The procedure or steps for media development go through four stages, namely: (1) the pre-development (preparation) stage, (2) the product development stage, (3) the product trial stage, and (4) the post-development stage. The finished 2-dimensional animated video product is then validated by media experts, material experts, librarians. The finished product is then tested on 30 students of SMA Negeri 8 Malang. The results showed that the assessment of media experts, material experts, and librarians gave the criteria "Very Valid", and the results of field trials on students gave the criteria "Very Valid". In addition to providing an assessment, the validator also provides product improvement suggestions. Based on the results of the research conducted, it can be concluded that the library promotion product based on 2-dimensional animated video which was developed after being revised shows the criteria of "Very Valid" so that the 2-dimensional animated video is feasible to use. Keywords: school library, library promotion, 2D animation video Abstrak: Perpustakaan berperan sebagai pusat sumber belajar warga sekolah dengan menyediakan bahan pustaka sebagai penunjang pembelajaran. Namun, perpustakaan sekolah kurang dimanfaatkan dengan baik sebagai penunjang pembelajaran. Tujuan penelitian dan pengembangan ini yaitu menghasilkan produk promosi perpustakaan berbasis video animasi 2D yang memenuhi aspek kelayakan, ketepatan, dan kemenarikan. Produk video animasi 2D dibuat dengan materi manfaat membaca dan program 15 menit membaca di sekolah. Penelitian ini menggunakan model penelitian dan pengembangan R&D Borg dan Gall. Prosedur atau langkah-langkah pengembangan media melalui empat tahap, yaitu: (1) tahap prapengembangan (persiapan), (2) tahap pengembangan produk, (3) tahap uji coba produk, dan (4) tahap pascapengembangan. Produk video animasi 2 dimensi yang telah jadi kemudian divalidasi oleh ahli media, ahli materi, pustakawan. Produk yang sudah jadi kemudian diuji cobakan kepada 30 siswa SMA Negeri 8 Malang. Hasil penelitian menunjukkan penilaian dari ahli media, ahli materi, dan pustakawan memberikan kriteria “Sangat Valid”, dan hasil uji coba lapangan pada siswa memberikan kriteria “Sangat Valid”. Selain memberikan penilaian, validator juga memberikan saran perbaikan produk. Berdasarkan hasil penelitian yang dilakukan, dapat disimpulkan bahwa produk promosi perpustakaan berbasis video animasi 2 dimensi yang dikembangkan setelah direvisi menunjukan kriteria “Sangat Valid” sehingga video animasi 2 dimensi layak digunakan. Kata Kunci: perpustakaan sekolah, promosi perpustakaan, video animasi 2D